The discovery of the endocrine heart - Bold, Adolfo J. de (2018)
To travel down the memory lane with reference to the discovery of the atrial natriuretic factor (ANF) and hence of the endocrine function of the heart is a slippery slope. It is so because it takes me down to my very young years during which, somehow, I had decided to be a research scientist. And now I realize that this had nothing to do with my education, family influences or role models. It was just that: one wants to be a scientist since very early in life and nobody, including you, knows exactly why. Call it a vocation. With that emotional package in hand I parted after completing my secondary education from my natal city of Parana, Entre Rios to Rosario, Santa Fe to study to become a clinical biochemist. Why biochemistry and not medicine? Because I somehow knew that biochemistry would provide a biomedical scientist with more basic tools that medicine would. How did I know that? I don't know. And here comes the part where the Providence really starts to show its hand.